Ultrastable and High‐Rate 2D Siloxene Anode Enabled by Covalent Organic Framework Engineering for Advanced Lithium‐Ion Batteries. Issue 6 (27th April 2022) - Zhang, Yuchan; Wu, Yang; An, Yongling; Wei, Chuanliang; Tan, Liwen; Xi, Baojuan; Xiong, Shenglin; Feng, Jinkui
Abstract: Siloxene as a new type of 2D material has wide potential applications due to its special structure. Especially, as anode for lithium‐ion batteries, siloxene shows promising prospect due to its small volume change and low diffusion pathway. However, the unstable solid electrolyte interphase and low electronic conductivity lead to the low Coulombic efficiency, poor rate capability, and limited cycling performance. To settle the problems, a thin porous covalent organic framework (COF) coating layer is designed by in situ growth on micro‐sized siloxene. With the inherent ionic conductive and electrolyte compatible advantages of COF, the engineered siloxene demonstrates superior electrochemical performance with 96% capacity retention at 8 A g −1 for 1500 cycles. Abstract : A light‐weight covalent organic framework Tf‐TAPA with the inherent ionic conductive and electrolyte compatible advantages is designed to engineer 2D layered siloxene anode to achieve high rate and ultrastable Li‐ion battery. Through the porous COF coating layer engineered siloxene interface, this anode exhibits excellent cycling stability at a high current density 8 A g −1 and outstanding rate capability.